2019
DOI: 10.1021/acschembio.9b00679
|View full text |Cite
|
Sign up to set email alerts
|

Double Monoubiquitination Modifies the Molecular Recognition Properties of p15PAF Promoting Binding to the Reader Module of Dnmt1

Abstract: The proliferating cell nuclear antigen (PCNA)-associated factor p15PAF is a nuclear protein that acts as a regulator of DNA repair during DNA replication. The p15PAF gene is overexpressed in several types of human cancer, and its function is regulated by monoubiquitination of two lysines (K15 and K24) at the protein N-terminal region. We have previously shown that p15PAF is an intrinsically disordered protein which partially folds upon binding to PCNA and independently contacts DNA through its N-terminal tail.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…These structural features are also consistent with the fact that early replicating domains contain a much higher degree of DNA methylation at which time PAF15Ub2 is predominantly recruiting DNMT1. We also note that, during the revision of our manuscript, a recent study has also shown that full-length hPAF15Ub2 binds DNMT1 in vitro 49 .…”
Section: Discussionmentioning
confidence: 70%
“…These structural features are also consistent with the fact that early replicating domains contain a much higher degree of DNA methylation at which time PAF15Ub2 is predominantly recruiting DNMT1. We also note that, during the revision of our manuscript, a recent study has also shown that full-length hPAF15Ub2 binds DNMT1 in vitro 49 .…”
Section: Discussionmentioning
confidence: 70%
“…The monoubiquitination of lysine residues 15 and 24 by UHRF1 in the N-terminal tail of p15 appears to be extremely important. Recently, an extensive structural and conformational characterization of doubly monoubiquitinated p15 showed that it remains disordered and binds PCNA in the same way as non-ubiquitinated p15, but binds DNA with a 5-fold reduced affinity [55], which supports the previously proposed hypothesis of p15 modulating the velocity with which PCNA slides along DNA [54]. Moreover, calorimetry experiments revealed that the double monoubiquitination mark of p15 is recognized by the RFTS domain of DNA methyl transferase 1, indicating a role of p15 in the regulation of DNA methylation maintenance.…”
Section: The Unique Interaction Of Pcna With P15mentioning
confidence: 99%
“…Moreover, monoubiquitination and multi‐monoubiquitination have been reported to regulate protein–protein interactions. For example, doubly monoubiquitinated p15PAF interacts directly with PCNA and facilitates the recruitment of Dnmt1 to maintain DNA methylation during DNA replication . Similarly, Zhang et al.…”
Section: Monoubiquitination and Multi‐monoubiquitination: Regulator Omentioning
confidence: 97%